Analysis of Junior High School Students' Numeracy Literacy in Solving Minimum Competency Assessment Model (AKM) Questions on Number Content - Danis, Hayati Nufus; Khaerunnisa, Etika; Hendrayana, Aan (Al-Khawarizmi, 2024)
This research aims to describe and analyze the numeracy literacy abilities of junior high school students in solving AKM model questions on number content. The type of research used in this research is descriptive qualitative research. The research subjects studied were 36 students in class VII-G of SMP Negeri 7 Serang City who had received material on whole numbers and fractions. The research instrument used was the AKM model questions consisting of three descriptive questions which had been adjusted to the numeracy literacy indicators. The written test results were analyzed based on numeracy literacy indicators and then strengthened by the results of student interviews. The research results show that students' numeracy literacy skills in solving AKM model questions on number content are still not good. Because students are unable to meet the three numeracy literacy indicators. Students' numeracy literacy abilities are predominantly in the medium category. In solving AKM model questions on number content, students with high and moderate abilities experienced calculation errors in the results of addition, subtraction, multiplication and division. Students with low abilities have difficulty determining solution strategies and understanding the concept of arithmetic operations of addition, subtraction, multiplication and division on whole numbers and fractions as well as in calculating discounts.